ANALISIS PEMBELAJARAN â€œDARINGâ€ PADA GURU SEKOLAH DASAR DI ERA COVID-19 - Wulandari, Medita Ayu; Arga, Hana Sakura Putu; Kelana, Jajang Bayu; Altaftazani, Deden Herdiana; Ruqoyyah, Siti (IKIP Siliwangi Bandung, 2020)
The background of this research is to see the effectiveness of learning carried out in elementary schools since the Covid-19 pandemic hit. All face-to-face learning activities that are usually carried out in schools are transformed into online-based learning and have various impacts on elementary school teachers in delivering learning material. The research objective was to analyze the effectiveness of learning carried out by elementary school teachers during the Covid-19 pandemic. This study used a descriptive method with the research subjects teacher of grade 1-6 Girimukti elementary school, Cipatat district. The research instrument used was an open questionnaire, interviews, documents, and field notes. The results of the study show that ineffective learning is applied to elementary school students due to inadequate facilities and infrastructure such as smartphones and stable internet networks that affect teachers in the learning process. Also, the participation of parents and the unpreparedness of parents in the accompanying learning process.